Digital legacy: Designing with things. Issue 7 (9th August 2019) - Pitsillides, Stacey
Abstract: This paper explores how theories of things can create new forms of agency for the dead. It considers how meaning is constructed through the use or translation of our diverse collections and environments online. These memorials and rituals offer a plurality of narratives, experiences and esthetics, which have the potential to give a wider scope for constructing a durable biography after death. The paper draws conceptual links between digital and physical materials and aims to expand interdisciplinary discourse around the way design can create new forms of legacy through rethinking the role of digital things in our lives.